(untitled) (Texas Journal of Philology, Culture and History, 2025)
This article analyzes the pressing issues of developing the aesthetic thinking of youth within the process of spiritual renewal of society from a philosophical and aesthetic perspective. In particular, the role, impact, and prospects of modern socio-cultural technologies in this process are examined in depth. Aesthetic thinking is not only the ability to perceive and appreciate beauty but also a powerful means of nurturing the inner world of an individual and spiritually awakening them.